Physiological short-term response to sudden salinity change in the Senegalese sole (Solea senegalensis) - Herrera, M. (2014)
The physiological responses of Senegalese sole to a sudden salinity change were investigated. The fish were first acclimated to an initial salinity of 37.5 ppt for 4 h. Then, one group was subjected to increased salinity (55 ppt) while another group was subjected to decreased salinity (5 ppt). The third group (control group) remained at 37.5 ppt. We measured the oxygen consumption rate, osmoregulatory (plasma osmolality, gill and kidney Na+,K+-ATPase activities) and stress (plasma cortisol and metabolites) parameters 0.5 and 3 h after transfer. Oxygen consumption at both salinities was higher than for the control at both sampling times. Gill Na+,K+-ATPase activity was significantly higher for the 55 ppt salinity at 0.5 h. Plasma osmolality decreased in the fish exposed to 5 ppt at the two sampling times but no changes were detected for high salinities. Plasma cortisol levels significantly increased at both salinities, although these values declined in the low-salinity group 3 h after transfer. Plasma glucose at 5 ppt salinity did not vary significantly at 0.5 h but decreased at 3 h, while lactate increased for both treatments at the first sampling time and returned to the control levels at 3 h. Overall, the physiological response of S. senegalensis was immediate and involved a rise in oxygen consumption and plasma cortisol values as well as greater metabolite mobilization at both salinities.